Answer:
x = 3, 1
Explanation:
x² - 4x + 3 = 0
First we need to subtract 3 from both sides of the equation.
x² - 4x = -3
Next, we need to take b (which is represented by -4 here) and plug it into the equation:
![((b)/(2)) ^(2)](https://img.qammunity.org/2021/formulas/mathematics/college/zher7c3m9x9vog5vtx2crmuycg2r9nkazq.png)
= (-2)²
Plug this into our equation.
x² - 4x + (-2)² = -3 + (-2)²
Simplify.
x² - 4x + (-2)² = -3 + (-2)²
x² - 4x + 4 = -3 + 4
x² - 4x + 4 = 1
Next we factor this.
x² - 4x + 4 = 1
(x - 2)(x - 2) = 1
(x - 2)² = 1
Now we solve for x. Take the square root of both sides.
√(x - 2)² = ±√1
x - 2 = ±√1
Square root of 1 is 1: √1 = 1
x - 2 = ±1
We're going to have two different solutions.
x - 2 = 1
x = 3
OR
x - 2 = -1
x = 1
Thus, x = 3, 1